Isolation and Genome Analysis of Pectobacterium colocasium sp. nov. and Pectobacterium aroidearum, Two New Pathogens of Taro - Zhou, Jianuan; Hu, Ming; Hu, Anqun; Li, Chuhao; Ren, Xinyue; Tao, Min; Xue, Yang; Chen, Shanshan; Tang, Chongzhi; Xu, Yiwu; Zhang, Lianhui; Zhou, Xiaofan (Frontiers in Plant Science, 2022)
Bacterial soft rot is one of the most destructive diseases of taro (Colocasia esculenta) worldwide. In recent years, frequent outbreaks of soft rot disease have seriously affected taro production and became a major constraint to the development of taro planting in China. However, little is known about the causal agents of this disease, and the only reported pathogens are two Dickeya species and P. carotovorum. In this study, we report taro soft rot caused by two novel Pectobacterium strains, LJ1 and LJ2, isolated from taro corms in Ruyuan County, Shaoguan City, Guangdong Province, China. We showed that LJ1 and LJ2 fulfill Koch's postulates for taro soft rot. The two pathogens can infect taro both individually and simultaneously, and neither synergistic nor antagonistic interaction was observed between the two pathogens. Genome sequencing of the two strains indicated that LJ1 represents a novel species of the genus Pectobacterium, for which the name "Pectobacterium colocasium sp. nov." is proposed, while LJ2 belongs to Pectobacterium aroidearum. Pan-genome analysis revealed multiple pathogenicity-related differences between LJ1, LJ2, and other Pectobacterium species, including unique virulence factors, variation in the copy number and organization of Type III, IV, and VI secretion systems, and differential production of plant cell wall degrading enzymes. This study identifies two new soft rot Pectobacteriaceae (SRP) pathogens causing taro soft rot in China, reports a new case of co-infection of plant pathogens, and provides valuable resources for further investigation of the pathogenic mechanisms of SRP.